Hallazgo de aleaciones metálicas de Cu-Zn (Grupo de la Zinccoperita) en el sistema epitermal Farallón Negro-Alto de la Blenda, provincia de Catamarca, Argentina - Wernert, Matías Sebastián (2019)
Findings and descriptions of metallic Cu-Zn alloys, such as the zinccopperite proposed in this work, are sparsely documented worldwide. The discovery of these compunds in various rocks from Farallón Negro-Alto de la Blenda (FN-AB) gold-silver mine represents an original contribution towards the deposit’s mineralogy and also establishes the first mention of Cu-Zn alloys in Argentina. The alloy was determined by reflected-light microscope and scanning electron microscope (SEM) with energy-dispersive spectroscopy (EDS). The results reveal for each detected element a compositional range (%wt) of Cu: 61,91-74,55; Zn: 23,99-37,99; S: 0-1,66; Fe: 0- 0,43 and Sn: 0-1,55. These values, on average, yield to an approximate chemical formula of Cu2,00Zn, indicating that the compound belongs to the α phase of Cu-Zn alloys. The chemical and optical aspects are similar to those informed by Xiao et al. (1998) and Xie et al. (2006) for zinccopperite found in Chinese localities. Furthermore, by taking into account textural and paragenetical characteristics, as well as the geological setting in which the alloy was found, zinccopperite is interpreted as a late product of the hydrothermal activity responsible for ore mineralization in FN-AB deposit.